(5a –3b) (a + b)
right one will mark as brainlist
Answers
Answered by
1
Answer:
Simplifying
(5a + -3b)(a + b) = 0
Multiply (5a + -3b) * (a + b)
(5a * (a + b) + -3b * (a + b)) = 0
((a * 5a + b * 5a) + -3b * (a + b)) = 0
Reorder the terms:
((5ab + 5a2) + -3b * (a + b)) = 0
((5ab + 5a2) + -3b * (a + b)) = 0
(5ab + 5a2 + (a * -3b + b * -3b)) = 0
(5ab + 5a2 + (-3ab + -3b2)) = 0
Reorder the terms:
(5ab + -3ab + 5a2 + -3b2) = 0
Combine like terms: 5ab + -3ab = 2ab
(2ab + 5a2 + -3b2) = 0
Solving
2ab + 5a2 + -3b2 = 0
Solving for variable 'a'.
Factor a trinomial.
(5a + -3b)(a + b) = 0
Answered by
1
Step-by-step explanation:
(5a-3b)(a+b)
5a(a+b)-3b(a+b)
5a²+5ab-3ab+3b²
5a²+2ab-3b²
Similar questions